Correlation of Serum Prolactin and Thyroid Hormone in Female Infertility - Banu, Fahat (Journal of Nepalgunj Medical College, 2019)
Background: Infertility is a growing problem with adverse medical, social and psychological consequences globally. Apart from several causes of infertility, hormonal imbalance especially thyroid dysfunction and hyperprolactinemia can lead to female infertility. Both these conditions are treatable so Proper management of hormonal imbalance can result in restoration of normal fertility. Aims and objectives: Correlation of serum Prolactin and Thyroid hormone in female infertility. Materials and methods: Descriptive hospital based study was conducted at Nepalgunj medical college and teaching hospital, Nepalgunj, Banke, Nepal. The data was collected from September 2018 to August 2019. Total 30 cases of females of primary and secondary infertility attending outpatient department of gynecology department of Nepalgunj medical college were included in the study. A detailed history and clinical evaluation was done along with estimation of serum Prolactin and Thyroid hormone profile. Result: Hormonal status of subjects showed 15 i.e. 50% participants were thyroid whereas 11 (36.33%) were hypothyroid and 4 (13.33%) were hyperthyroid. Serum Prolactin was raised in 17 (57%) and normal in 13 (43%). Serum TSH and prolactin were found to be significantly positively correlated in female infertility (r=0.507, p =0.004). Conclusion: There is a high incidence of hyperprolactinaemia and thyroid dysfunction in female infertility.